Nutritional compositions and antioxidative capacity of the silk obtained from immature and mature corn - Abdul Rahman, Nurhanan; Wan Ishak, Wan Rosli (Elsevier & King Saud University, 2014)
The silks of immature and mature corn were evaluated for their variations in nutritional compositions, mineral content and antioxidant capacity. Both immature and mature silks were good source of nutritional compositions. Immature silks contained significantly higher moisture (89.31%) (fresh basis), lipid (1.27%) and protein (12.96%) content than the mature silk. Mature silks contained higher composition of ash (5.51%), carbohydrate (29.74%) and total dietary fiber (51.25 g/100 g), than the immature silk, but the difference was not significant. In mineral determination, immature silk was rich source of Ca (1087.08 μg/g), Mg (1219.17 μg/g), Cu (5.60 μg/g) and Zn (46.37 μg/g) than the mature silks. In contrast, other minerals such as K (35671.67 μg/g), Na (266.67 μg/g), Fe (4.50 μg/g) and Mn (35.57 μg/g) were found higher in the mature silk. The silks were extracted with ethyl acetate, ethanol and water using the Soxhlet extraction method to determine the polyphenol and ABTS radical scavenging capacity. From this study, the highest content of total polyphenol of immature silks was exhibited by ethanol extract (92.21 mg GAE/g) while water extract (64.22 mg GAE/g) had the highest polyphenol content among mature silk extracts. Total flavonoid content of both immature and mature silks was higher in the water extract at 8.40 mg CAE/g and 2.31 mg CAE/g, respectively. In the ABTS free radical assay method, all immature silk extracts had higher percentage of inhibition compared to the mature silks. Among all three crude extracts, the ethanol extract of immature (EC50 = 0.478 mg/ml) and mature silk (EC50 = 0.799 mg/ml) exhibited the strongest antioxidant capacity followed by the water and ethyl acetate extract.